2021
DOI: 10.3389/fonc.2021.641359
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Characterization of Cortical and White Matter Microstructural Pathology in Growth Hormone-Secreting Pituitary Adenoma

Abstract: BackgroundThe growth hormone (GH) and insulin-like-growth factor 1 (IGF-1) axis has long been recognized for its critical role in brain growth, development. This study was designed to investigate microstructural pathology in the cortex and white matter in growth hormone-secreting pituitary adenoma, which characterized by excessive secretion of GH and IGF-1.Methods29 patients with growth hormone-secreting pituitary adenoma (acromegaly) and 31 patients with non-functional pituitary adenoma as controls were recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Webb et al [22] found FA were significantly lower in the isolated growth hormone deficiency group. Yuan and his colleagues [23] reported long-term persistent and excess serum GH/IGF-1 levels alter the microstructure in white matter in growth hormonesecreting pituitary adenoma (acromegaly), and found lower fractional anisotropy (FA) and higher mean diffusivity (MD), in extensive bundles in acromegaly compared to non-functional pituitary adenoma controls. More research on association of brain white matter and GH/IGF-1 levels needed to be conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Webb et al [22] found FA were significantly lower in the isolated growth hormone deficiency group. Yuan and his colleagues [23] reported long-term persistent and excess serum GH/IGF-1 levels alter the microstructure in white matter in growth hormonesecreting pituitary adenoma (acromegaly), and found lower fractional anisotropy (FA) and higher mean diffusivity (MD), in extensive bundles in acromegaly compared to non-functional pituitary adenoma controls. More research on association of brain white matter and GH/IGF-1 levels needed to be conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, considerable attention has been directed to the impairment of brain function in acromegaly ( 25 ). Some studies demonstrated that a considerable proportion of patients with acromegaly perform below average in several cognitive tests, particularly in the domains of attention and memory ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…This finding was confirmed by Yuan et al [ 71 ] in 2020, further finding a decrease in cerebrospinal fluid volume (CSFV) and that these changes significantly correlated with serum GH and IGF-1 levels. A subsequent in-depth study by Yuan et al [ 36 ] showed a general decrease in T1/T2 weighted ratio in most cortical and white matter in patients with acromegaly, implying extensive cortical and white matter demyelination and myelin regeneration. Alterations in structures such as the cerebral cortex, gray matter, and white matter may be responsible for neuropsychological dysfunction, including cognitive impairment, in patients.…”
Section: Mechanism Of Excess Gh and Igf-1 In Cognitive Impairmentsmentioning
confidence: 99%